The Prevalence and Antimicrobial Susceptibility Pattern of Gram-Positive Pathogens: Three-Year Study at a Tertiary Care Hospital in Mumbai, India - Shah, Sweta; Rampal, Ritika; Thakkar, Pooja; Poojary, Sushima; Ladi, Shweta (Journal of Laboratory Physicians, 2021)
Introduction The growing resistance pattern of the gram-positive pathogens along with a steady increase in minimum inhibitory concentration of the currently available antibiotics have led to an increase in morbidity and mortality rates in India. This study aims to access the shifting antibiotic susceptibility paradigm of the gram-positive pathogens in various infections at a tertiary care center.Methods This is a 3-year retrospective observational study which was performed from January 2016 to December 2018 at a tertiary care hospital in Mumbai. All clinically significant gram-positive cocci isolated from a variety of clinical specimens were studied for their prevalence and antimicrobial susceptibility.Results Out of 4,428 gram-positive isolates, Staphylococcus aureus (35.3%) was the commonly encountered pathogen, followed by Enterococcus spp. (32.1%) and coagulase-negative Staphylococcus (CoNS) (25.7%). S. aureus was majorly isolated from skin and soft tissue infections (60.3%), followed by patients with respiratory tract infections (18.2%) and blood stream infections (13%). Among S. aureus, particularly methicillin-resistant S. aureus (MRSA), prevalence increased from 29.5% in 2016 to 35.1% in 2018, with an overall prevalence of 33.6%. All S. aureus isolates were 100% sensitive toward vancomycin, linezolid, tigecycline, and teicoplanin. However, the CoNS isolates showed a higher resistance rate with reduced susceptibility toward linezolid and teicoplanin. High prevalence of resistance was observed across gram-positive isolates with commonly used antibiotics such as ciprofloxacin, levofloxacin, and erythromycin. While the prevalence of linezolid-resistant enterococcus (LRE) was 3.6%, vancomycin (VRE) and teicoplanin resistance among the enterococcus species was as high as 7.7% and 7.5%, respectively.Conclusion Rising methicillin resistance among the Staphylococcal species (MRSA and MR-CoNS) along with reduced susceptibility toward currently available anti-MRSA agents is a matter of serious concern as it limits the therapeutic options for treating multidrug resistant (MDR) gram-positive infections.
Keywords: gram-positive pathogens; Staphylococcus aureus; vancomycin-resistant enterococcus; coagulase-negative staphylococci; MRSA